Overtourism and Cultural Commodification in Thailand: A Critical Analysis of Sustainable Tourism Management Practices - Chansirisira, Pacharawit; Kenaphoom, Sanya; Kositsuriyapan, Chaimongkol (International Journal of Multidisciplinary in Management and Tourism, 2026)
Tourism has been a major driver of Thailand’s economic growth over the past twenty years, having a big effect on jobs, national income, and regional development. However, the rapid expansion of tourism has raised concerns about overtourism, damage to the environment, and changes to native customs in many popular tourist spots. Even if national policy frameworks call for sustainable tourism, overtourism is still a concern. This suggests that the issue may be linked to more than simply the number of tourists; it may also be linked to the way tourism is governed and planned for. This study aims to examine the structural elements that lead to overtourism in Thailand, analyze the processes of cultural commodification resulting from mass tourism, and critically evaluate current rules for sustainable tourism management. The research utilizes a qualitative documentary research methodology. Data were collected from national tourist development plans, policy documents from the Ministry of Tourism and Sports and the Tourism Authority of Thailand, reports from international organizations, academic literature, and tourism statistics published between 2000 and 2025. The data underwent theme analysis and critical discourse analysis to identify policy narratives, governance frameworks, and developmental objectives influencing tourism growth. The findings indicate that overtourism in Thailand is not solely attributable to elevated tourist numbers but is closely connected to a growth-oriented tourism paradigm characterized by centralized administration and policy objectives that prioritize visitor arrivals and tourism revenue. These structural reasons also make it easier for cultural commercialization to happen, which is when local customs and traditions are slowly turned into tourism products that can be sold. The research emphasizes the importance of institutional reforms, including decentralized tourism governance, improved regulatory frameworks, and heightened community engagement, to more successfully align tourism development with long-term sustainability.